2002
DOI: 10.1063/1.1524014
|View full text |Cite
|
Sign up to set email alerts
|

Role of group V exchange on the shape and size of InAs/InP self-assembled nanostructures

Abstract: We have studied the influence of Group V overpressure on the final shape and size of InAs nanostructures grown on ͑001͒ InP substrates. The mechanisms leading to postgrowth modifications in the InAs nanostructures are discussed. The simultaneous action of Group V overpressure and stress field-produced by the InAs nanostructures-can induce strong material transport. The direction of this material net current depends on the type of Group V element used for the overpressure flux. In situ reflection high-energy el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 17 publications
4
24
0
2
Order By: Relevance
“…5.1), where the dots were grown on InGaAsP, supports this explanation (As/P exchange is reduced on an InGaAsP surface) [90]. Similar observations have been previously reported for InAs QDs grown on (001) InP, and explained in a similar way [92]. Figure 5.32 is representative of what was observed when CLl was 2 or 3 nm thick.…”
Section: Double Capping Processsupporting
confidence: 75%
“…5.1), where the dots were grown on InGaAsP, supports this explanation (As/P exchange is reduced on an InGaAsP surface) [90]. Similar observations have been previously reported for InAs QDs grown on (001) InP, and explained in a similar way [92]. Figure 5.32 is representative of what was observed when CLl was 2 or 3 nm thick.…”
Section: Double Capping Processsupporting
confidence: 75%
“…The InAs/InP system differs from the InAs/GaAs one because group V atoms rather than the group III atoms are changed between the QDs and the buffer layer. A significant As/P exchange occurs at the InAs/InP interfaces [6,7]. In previous papers [8,9], a two-step capping layer growth method has been proposed, which allows the control of emission wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…This was required since the buried dots tend to become shorter compared to the surface dots due to exposure to P flux during capping [59] which causes the InP adatoms (formed at the top layer of InAs) to migrate towards the region in between the Qdots due to the strain mismatch. This process was further improved by a double capping procedure [60], introduced by Ledentsov et al [61] and Gutierrez et al [62] on InAs/GaAs and InAs/InP Qdots, respectively, as shown in Fig. 10(b).…”
Section: Qdots On (100) Inp Substratementioning
confidence: 99%